2019
DOI: 10.1021/acs.nanolett.9b03988
|View full text |Cite
|
Sign up to set email alerts
|

Yu–Shiba–Rusinov States in the Charge-Density Modulated Superconductor NbSe2

Abstract: NbSe2 is a remarkable superconductor in which charge-density order coexists with pairing correlations at low temperatures. Here, we study the interplay of magnetic adatoms and their Yu-Shiba-Rusinov (YSR) bound states with the charge density order. Exploiting the incommensurate nature of the charge-density wave (CDW), our measurements provide a thorough picture of how the CDW affects both the energies and the wavefunctions of the YSR states. Key features of the dependence of the YSR states on adsorption site r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 54 publications
3
68
0
Order By: Relevance
“…Therefore, the leading features of the YSR state are not affected by the CDW pattern. We notice a systematic study on the correlation between the CDW pattern and the YSR states has been reported very recently [28].…”
mentioning
confidence: 61%
“…Therefore, the leading features of the YSR state are not affected by the CDW pattern. We notice a systematic study on the correlation between the CDW pattern and the YSR states has been reported very recently [28].…”
mentioning
confidence: 61%
“…[9][10][11][12][13][14][15][16] The YSR states are very sensitive to the immediate environment of the impurity spin and give information on the role of the local environment on the exchange interaction J of an impurity spin with a superconductor. 3,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The bulk of recent experimental work on YSR states on superconducting (SC) substrates has demonstrated that the strength of the exchange interaction J can be significantly influenced by a small change in the adsorption site of the impurity or by spacers between the impurity and substrate. 3,18,[25][26][27][28][29][30][31][32][33][34] with α proportional to J, α = πρJS/2, where ρ is the normal-state density of states of the substrate at the Fermi level and S is the impurity spin.…”
mentioning
confidence: 99%
“…3,7,12,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] The bulk of recent experimental work on YSR states on superconducting (SC) substrates has demonstrated that the strength of the exchange interaction J can be significantly influenced by a small change in the adsorption site of the impurity or by spacers between the impurity and substrate. 3,18,[25][26][27][28][29][30][31][32][33][34] with α proportional to J, α = πρJS/2, where ρ is the normal-state density of states of the substrate at the Fermi level and S is the impurity spin. The bound state results from the spin-dependent scattering of Bogoliubov quasiparticles on the impurity and is thus associ-ated with the longitudinal part of the exchange interaction, JS z s z , where s represents the spin-density of the substrate electrons at the impurity position.…”
mentioning
confidence: 99%
“…Thus, while our model is expected to be most faithful in monolayer systems, the experimental evidence suggests it can reasonably capture the qualitative behavior of the top layer in contact with the magnet in multilayer systems. In a recent experiment examining Shiba states of Fe impurities in NbSe2 ( [34]), it was observed that the subgap energy of single magnetic impurity states may get modulated by the presence of the charge density wave (CDW). In the magnetic island structure we study (see figure 1 for a schematic view), similar effect could perhaps give rise to modulation of magnetically induced subgap bands with CDW periodicity.…”
Section: Modelmentioning
confidence: 99%